Detection of ancient DNA of Encephalitozoon intestinalis (Microsporidia) in archaeological material - Myšková, Eva; Ditrich, Oleg; Sak, Bohumil; Kváč, Martin; Cymbalak, Tomasz (The Journal of parasitology, 2014)
Ancient DNA (aDNA) of Encephalitozoon intestinalis (Microsporidia, Fungi) was detected in archaeological material originated from New Town of Prague (Czech Republic) with the use of molecular methods. Microsporidial aDNA was found in 3 samples originating from 2 objects, in a well/cesspit (samples from layers from the 18th century) and in a well from the 18th/19th century. The ability to use molecular methods to detect microsporidia extends the range of paleoparasitological inquiry, and could contribute to a better understanding of parasites shared between human and animals.
Keywords: Base Sequence; Czech Republic; Humans; lidé; sekvence nukleotidů; Molecular Sequence Data; History, 19th Century; Česká republika; dějiny 18. století; encephalitozoonóza; History, 18th Century; Animals; dějiny 19. století; Encephalitozoonosis; zvířata; DNA, Fungal; molekulární sekvence - údaje; DNA fungální; Encephalitozoon